Positron Annihilation Spectroscopy Study of Metallic Materials after High-Speed Cutting; Materials; Vol. 15, iss. 3 - Li Jinquan; Laptev R. S. Roman Sergeevich; Bordulev Yu. S. Yuri Sergeevich; Semek K. Kshishtof; Horodek P. Pawel; Shen H. Haolun; Lomygin A. D. Anton Dmitrievich; Cui Jian (2022, 2022)
Title screen